Arch translocation and the intra-arch elephant-trunk technique with collared graft for extended chronic dissecting aortic aneurysm - Ikenaga Shigeru (Journal of Cardiothoracic Surgery, 2013)
Abstract Management of extensive, chronic, dissecting aortic aneurysms after prior repair of the ascending aorta presents a technical challenge for surgeons. A symptomatic 64-year-old patient was admitted for elective surgical repair of an aortic annular dilatation, causing severe aortic regurgitation, and a Crawford type II extended thoracoabdominal aneurysm, 4 years after he underwent primary repair of an acute aortic dissection. The aorta was diffusely dilated, and there were no sites beyond the distal aortic arch where anastomosis could be performed. We successfully performed total aortic replacement with a 2-stage strategy, using an arch translocation technique and an intra-arch elephant-trunk technique.